2019
DOI: 10.1002/aenm.201803677
|View full text |Cite
|
Sign up to set email alerts
|

Relating Frontier Orbital Energies from Voltammetry and Photoelectron Spectroscopy to the Open‐Circuit Voltage of Organic Solar Cells

Abstract: For 19 diketopyrrolopyrrole polymers, the highest occupied molecular orbital (HOMO) energies are determined from i) the oxidation potential with square-wave voltammetry (SWV), ii) the ionization potential using ultraviolet photoelectron spectroscopy (UPS), and iii) density functional theory (DFT) calculations. The SWV HOMO energies show an excellent linear correlation with the open-circuit voltage (V oc ) of optimized solar cells in which the polymers form blends with a fullerene acceptor ([6,6]-phenyl-C 61 -b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 64 publications
(173 reference statements)
8
89
0
Order By: Relevance
“…We fit the experimental dark current densities using E g,fit , σ int,h , and A i ,fit as fitting parameters (Table ). The E g,fit values match very well to the expected E g , within the experimental error of the UPS data (≈0.1 eV) . We found that when σ int was set equal to σ b , the experimental activation barriers would not be reproduced correctly.…”
Section: Jd R and Eqe Of Bhj Opds Measured At V = −2 V At Photon Ensupporting
confidence: 64%
See 2 more Smart Citations
“…We fit the experimental dark current densities using E g,fit , σ int,h , and A i ,fit as fitting parameters (Table ). The E g,fit values match very well to the expected E g , within the experimental error of the UPS data (≈0.1 eV) . We found that when σ int was set equal to σ b , the experimental activation barriers would not be reproduced correctly.…”
Section: Jd R and Eqe Of Bhj Opds Measured At V = −2 V At Photon Ensupporting
confidence: 64%
“…Ultraviolet Photoelectron Spectroscopy : The UPS measurements were performed according to recently published methods and are further detailed in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this discrepancy lies in the experimental uncertainty in determining LUMO A and HOMO D , as their absolute value can depend on the measurement technique . As an example, the HOMO energy of PCDTBT was reported to be −5.5 or −5.4 eV .…”
Section: Why Does the Experimental Jd Deviate From Its Intrinsic Limit?mentioning
confidence: 99%
“…As an example, the HOMO energy of PCDTBT was reported to be −5.5 or −5.4 eV . Furthermore, reported LUMO energies of fullerene acceptors range between −4.3 and −3.8 eV . While these uncertainties might affect the results in Figure b, they would not explain deviations from the J d empirical limits by several orders of magnitude.…”
Section: Why Does the Experimental Jd Deviate From Its Intrinsic Limit?mentioning
confidence: 99%